A New Species of Cloacitrema (Digenea, Philophthalmidae) from Greater Flamingo (Phoenicopterus roseus) with Remarks on the Genera Cloacitrema and Pygorchis - Schuster, R.K. (Вестник зоологии, 2013)
Cloacitrema dubaiensis Schuster, sp. n. is described from four adult specimens found in the cloaca of greater flamingos in Dubai, UAE. It is the first Cloacitrema species found in the Afrotropic ecozone. The new species is medium-sized and slim, with the ventral sucker in equatorial position and the uterus that extends laterally to intestinal caeca. It has oval, unlobed, touching each other testes in parallel to slightly oblique position. C. dubaiensis resembles C. narrabeenensis but differs in body shape, position of acetabulum, size of the seminal vesicle and number of vitelline follicles and their extension lateral to caeca. Cloacitrema dubaiensis Schuster, sp. n. описывается по четырём взрослым экземплярам, обнаруженным в клоаке обыкновенных фламинго в Дубае (ОАЭ). Это первый вид Cloacitrema, найденный в Афротропическом регионе. Новый вид отличается средними размерами, удлинённой формой тела, экваториальным положением вентральной присоски и маткой, простирающейся латерально до ветвей кишечника. Семенники овальные, не разделенные на лопасти, касающиеся друг друга, лежащие параллельно, или слегка диагонально. Вид C. dubaiensis подобен C. narrabeenensis, но отличается от него формой тела, положением брюшной присоски, размером семенного пузырька, количеством желточников и их протяженностью латерально до уровня кишечных стволов.